External validation of prognostic models for preeclampsia in a Dutch multicenter prospective cohort - Marije Lamain-de Ruiter; Anneke Kwee; Christiana A. Naaktgeboren; Rebecca D. Louhanepessy; Inge De Groot; Inge M. Evers; Floris Groenendaal; Yolanda R. Hering; Anjoke J. M. Huisjes; Cornel Kirpestein; Wilma M. Monincx; Peter C. J. I. Schielen; et al. (Taylor & Francis Group, 2019)
Objective: To perform an external validation of all published prognostic models for first-trimester prediction of the risk of developing preeclampsia (PE). Methods: Women <14 weeks of pregnancy were recruited in the Netherlands. All systematically identified prognostic models for PE that contained predictors commonly available were eligible for external validation. Results: 3,736 women were included; 87 (2.3%) developed PE. Calibration was poor due to overestimation. Discrimination of 9 models for LO-PE ranged from 0.58 to 0.71 and of 9 models for all PE from 0.55 to 0.75. Conclusion: Only a few easily applicable prognostic models for all PE showed discrimination above 0.70, which is considered an acceptable performance.